Factors Affecting the Quality of Life of Patients After Kidney Transplantation: A Cross-Sectional Study - Maruhum Bonar Hasiholan Marbun; Dories Septiana; Hamzah Shatri; Ikhwan Rinaldi (Acta Medica Indonesiana)
Background: Kidney transplantation is currently the best choice for renal replacement therapy, due to its effect in reducing mortality and improving the quality of life (QoL) of patients with end-stage renal disease. This study aimed to identify factors affecting QoL after kidney transplantation. Methods: We conducted a cross sectional study by recruiting patients who had kidney transplantation at Cipto Mangunkusumo General Hospital, Jakarta, Indonesia, from 2018 – 2020. QoL was assessed using the 36-item Short Form Health Survey (SF-36) questionnaire. We evaluated age, sex, body mass index, hemoglobin level, estimated glomerular filtration rate, duration of dialysis before transplantation, history of diabetes, depression, and performance status as factors associated with QoL score. Results: We involved 107 subjects in our study. Depression, hemoglobin level, ECOG performance status, and duration of dialysis were factors affecting the physical component score (R2=0.21). Depression and hemoglobin level were factors affecting the mental component score (R2=0.34 ). Depression, hemoglobin level, and ECOG performance status were factors contributed to the total QoL score (R2=0.41). Conclusion: Factors that contributed to QoL status were depression, ECOG performance status, and hemoglobin levels. This study supported the need for assessment of QoL on regular basis, psychological aspects including depression, as well as other factors that can affect QoL such as performance status and hemoglobin level in patients before and after kidney transplantations.